Bernardo de Gálvez : Spanish Hero of the American Revolution - Quintero Saravia, Gonzalo M., 1964- (Book collections on Project MUSE., 2018)
Although Spain was never a formal ally of the United States during the American Revolution, its entry into the war tipped the balance against Britain. Led by Bernardo de Gálvez, supreme commander of the Spanish forces in North America, Spanish military campaigns against British settlements on the Mississippi River, and later against Mobile and Pensacola, were crucial in preventing Britain from concentrating all its North American military and naval forces on the fight against George Washington's Continental Army. This comprehensive biography of Gálvez (1746-86) examines in detail the commander's considerable historical impact and expands our understanding of Spain's contribution to the war.